2022
DOI: 10.1001/amajethics.2022.194
|View full text |Cite
|
Sign up to set email alerts
|

An Abolitionist Approach to Antiracist Medical Education

Abstract: Medical education is limited to the biomedical model, omitting critical discourse about racism, the harm it causes minoritized patients, and medicine's foundation and complicity in perpetuating racism. Against a backdrop of historical resistance from medical education leadership, medical students' advocacy for antiracism in medicine continues. This article highlights a medical student-led antiracist curricular effort that moves beyond a biomedical model and uses abolition as the guiding framework in the creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…80,81 Anti-racism training based in abolition medicine, critical race theory, and decolonization frameworks, rather than, "sanitized, apologetic frameworks centering White [individuals'] comfort and passivity, such as racial disparities and cultural competency.renders the invisibility of Whiteness visible to highlight its role in upholding medical racism and preventing change." 82 Addressing the cause of racial disparities is likely more effective than just focusing on the outcomes of racism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…80,81 Anti-racism training based in abolition medicine, critical race theory, and decolonization frameworks, rather than, "sanitized, apologetic frameworks centering White [individuals'] comfort and passivity, such as racial disparities and cultural competency.renders the invisibility of Whiteness visible to highlight its role in upholding medical racism and preventing change." 82 Addressing the cause of racial disparities is likely more effective than just focusing on the outcomes of racism.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of anti‐racism training as an Accreditation Council for Graduate Medical Education (ACGME) common program requirement is an actionable step to encourage learning environments to operationalize anti-racism. 81 As part of an anti-racism core competency, the history of U.S. slavery and its effect on medicine would highlight the, “false premise of racial groups as distinct biological populations…and the role of racism as a preventable etiology of racial health disparities.” 80 , 81 Anti-racism training based in abolition medicine, critical race theory, and decolonization frameworks, rather than, “sanitized, apologetic frameworks centering White [individuals'] comfort and passivity, such as racial disparities and cultural competency…renders the invisibility of Whiteness visible to highlight its role in upholding medical racism and preventing change.” 82 Addressing the cause of racial disparities is likely more effective than just focusing on the outcomes of racism.…”
Section: Discussionmentioning
confidence: 99%
“…Organized medicine increasingly recognizes how foundational this legacy is for challenging health inequities, 11 yet few prior examples of integration into medical school curricula exist. 23 The workshop demonstrated that covering this vast history in a 90-minute lecture is feasible, including when using a virtual format, and that this format can heighten students' self-reported knowledge and awareness of slavery's historical arcs of oppression, particularly related to forced scientific experimentation other than the Tuskegee Syphilis Study and how a narrative of racial difference influences diagnosis and treatment. Medical students' limited exposure to this legacy prior to attending this workshop reinforces the urgent need to address this educational gap.…”
Section: Discussionmentioning
confidence: 99%
“…It reimagines the work of medicine as an anti-racist practice by abolishing practices reinforcing biological race, desegregating the medical profession, demanding reparations for communities devastated by forced medical experimentation, and insisting on longitudinal anti-racism training rooted in the history of racism in medicine. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…Current pedagogical examples of interrogating structural racism, including the PIC, are limited (Chandler et al, 2022; Rice, 2022). However, there are some examples of public health faculty who teach courses related to the public health impacts of criminalization and mass incarceration (Duarte et al, 2020; Fullilove et al, 2020; Heller & Galea, 2020; Nowotny et al, 2020; Rice, 2022) as well as efforts in social work (James, 2021) and medicine (Asmerom et al, 2022) that integrate abolition into the curriculum. Echoing other recent calls, there is a need for academic public health to generate scholarship and train professionals on the population health consequences of the PIC and develop community-led strategies to reduce incarceration (Heller & Galea, 2020).…”
Section: Public Health and Abolitionmentioning
confidence: 99%